Loyalitas Tenaga Administrasi Pendidikan Dalam Menciptakan Layanan Pendidikan Di MI - Ahmad Tarmizi Hasibuan; Nanda Elza; Dinda Aisyah; Hanny Nabila Humairo (LPPM Politeknik Pratama, 2023)
Education is very important in shaping the good and bad of the human person. Realizing this, all educational units, both schools and madrasas, need educators and education staff according to the requirements and regulations in force so that they can carry out educational activities as they should. In this regard, the role of administrative staff is very important to support the smooth and successful administration of schools. Comprehensiveness that involves all parties to create a shared goal of realizing a higher quality school, administration is very important for each respective school from matters of curriculum, student affairs, staffing, finance and others. Administration in a broad sense is administration, administration is an all-encompassing process that involves all parties who realize common goals, while administration is a process of cooperation of all forces to create quality schools. While the administration of education is the guidance, supervision and implementation of everything related to school affairs.